Development of mayonnaise from duck egg - Bingil, Cherry Ferolin (2000)
The feasibility by using duck egg as an alternative to chicken egg in mayonnaise making was investigated.
Sotech thesis.
Keywords: Mayonnaise; Duck; Egg